2016
DOI: 10.1111/gfs.12272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant architecture and drought stress level on lucerne forage quality

Abstract: Breeding for enhanced quality in lucerne (Medicago sativa) frequently involves selection for higher leaf‐to‐stem ratio, multifoliolate leaves or short‐internode stems. Three populations selected for such alternative morphologies and a reference cultivar were evaluated for forage yield, leaf‐to‐stem ratio and protein and fibre concentrations in leaves, stems and whole plants. Four managed environments were obtained by combining two stress levels (moderate or nil) with two sowing times. The population selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…The importance of protein content and the weak concentration of proteins in the stems (e.g. 12.1% vs 26.5% in leaves across harvests [11]) encourages the exploitation of these SNPs for MAS, as well as the investigation of these potential candidate genes for stem protein content variation. In addition, GWAS highlighted a genomic area on chromosome 8 that was characterized by high concentration of SNP markers linked to ADL in leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of protein content and the weak concentration of proteins in the stems (e.g. 12.1% vs 26.5% in leaves across harvests [11]) encourages the exploitation of these SNPs for MAS, as well as the investigation of these potential candidate genes for stem protein content variation. In addition, GWAS highlighted a genomic area on chromosome 8 that was characterized by high concentration of SNP markers linked to ADL in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivar, maturity stage and harvest time all have an important effect on the main forage quality parameters [58]. Forage quality can also be affected by abiotic stresses, especially drought, through direct and indirect effects on plant morphology and physiology [911]. Various studies have revealed the presence of variation for forage quality traits, particularly within cultivars [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The first harvest (third for 2014 alfalfa) in the seeding year could have had lower crude protein since it was harvested in the summer and likely had higher stem to leaf ratio. Stems usually have much less protein than leaves [37]. This probably was the reason for the differences in crude protein concentration.…”
Section: Alfalfa Forage Nutritive Valuementioning
confidence: 99%
“…Research done in Italy concluded that alfalfa cultivars with the multifoliolate trait showed low expression of the trait under stress, reducing NDFD and crude protein. Alfalfa in drought stress environments had 12.3% lower plant NDF and 9.7% lower leaf protein [46]. Additionally, drought stress can have a direct negative effect on symbiotic N 2 fixation, which can reduce crude protein in alfalfa stems [47].…”
Section: Alfalfa Forage Nutritive Valuementioning
confidence: 99%